Teologi Warisan Perspektif Alkitab Dan Budaya Toraja adi Lembang Patongloan - Marni Ruru; Yawan Minaldi Paonganan (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
This paper conducts a study of the concept and meaning of heritage in the Bible and Toraja culture, specifically in Lembang Patongloan, to find out the theological meaning of heritage in the perspective of the Bible and also toraja culture. The purpose of this paper is to find the theological meaning of inheritance in the Bible and Toraja Culture in responding to various conflicts that arise regarding inheritance or mana' in the Patongloan lembang. The writing uses qualitative methods by conducting literature studies, and interviews directly at the Patongloan lembang. This research finds that theologically the legacy of the Biblical context and Toraja culture is a symbol of providence, the relationship between God and people, parents and children in pa'rapuan as a form of responsibility. Land inheritance has not only economic value, but also religious value. However, the social facts in Patongloan's lembang are violations of the rules and meaning of inheritance or mana'.